Candidates for downstream jets at interplanetary shocks - Hietala, H.; Trotta, D.; Fedeli, A; Wilson III, L. B.; Vuorinen, L.; Coburn, J. T. (Oxford University Press, 2025)
Localized dynamic pressure enhancements arising from kinetic processes are frequently observed downstream of the Earth’s bow shock. These structures, called jets, modify their plasma surroundings and participate in particle energization. Here, we report the first observations of jet-like structures in a non-planetary shock environment: downstream of interplanetary shocks. We introduce an analysis approach suitable for such conditions and apply it to Wind spacecraft data. We present one event with a Mach number similar to the Earth’s bow shock as a benchmark, as well as two low Mach number, low beta shocks: a parameter range that is difficult to access at planets. The jet-like structures we find are tens of ion inertial lengths in size, and some are observed further away from the shock than in a limited magnetosheath. We find that their properties are similar to those of magnetosheath jets: in the frame of the shock these structures are fast, cold, and most have no strong magnetic field variations. All three interplanetary shocks feature foreshock activity, but no strongly compressive waves. We discuss the implications, these findings have for the proposed jet formation mechanisms.